Student-Based Reflective Supervision to Assess the Effectiveness of PAI Learning - Asep Supriadi AA; Astuti Feriyanti; Riyanti Agustini; Siti Halimah (TA'DIB: Jurnal Pendidikan Agama Islam, 2026)
This article aims to examine the concept of student-based reflective supervision as an effective evaluative strategy in assessing the learning quality of Islamic Religious Education (PAI). The main focus is on how student involvement in providing reflective feedback can be leveraged by teachers and principals to improve teaching effectiveness. This study uses a library research method with a qualitative descriptive approach. Data was obtained from various sources, such as scientific journals, academic books, national education policies, and relevant study reports. All of these data were analyzed to build a conceptual framework of student-based reflective supervision. The results of the study show that reflective supervision involving students' perspectives can result in more authentic and contextual evaluation of learning. Feedback from students reflects their first-hand learning experiences, so it can be an important indicator in assessing the effectiveness of the strategies, methods, and learning media used by PAI teachers. This student-based reflective supervision also offers an alternative approach to evaluating the learning process, which has tended to be based only on assessments from superiors or outside parties. By making students partners in the reflection process, teachers and principals can gain a more comprehensive and human understanding of the success of teaching, especially in instilling Islamic values.